Porous silicon trench and capacitor structures - KENNEY; DONALD M; GEISS; PETER J (1997)
The invention provides a capacitor structure utilizing porous silicon as a first plate of the capacitor structure, thereby greatly increasing the surface area available for the capacitor and thereby the capacitance attainable. The invention also provides a trench structure having a porous silicon region surrounding the sidewalls thereof. Such a trench can then be utilized to form a capacitor according to the subject invention. Methods of producing the capacitor and trench structures according to the subject invention are also provided. Porous silicon is produced utilizing electrolytic anodic etching.